2015
DOI: 10.1590/s1677-5538.ibju.2014.0355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reactive stroma in prostate cancer: involvement of growth factors, metalloproteinase matrix, sexual hormones receptors and prostatic stem cells

Abstract: Introduction and Objectives:Reactive Stroma (RStr) is observed in many human cancers and is related to carcinogenesis. The objectives of the present study were to stablish a relationship of the RStr microenvironment with prostate cancer (Pca) through a morphological and molecular characterization, and to identify a possible relationship between RStr with worse prognosis factors and occurrence of malignant prostatic stem cells.Materials and Methods:Forty prostatic samples were selected from men with Pca diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…This indicates that reactive stroma content can provide additional information beyond the Grade Group system used for current patient prognosis assessment in prostate cancer, which is in line with previous studies 6 9 , 11 . However, RSG is not entirely independent of Grade Group, as illustrated by our correlation analysis and previous studies 7 , 11 , 14 . This suggest that a reactive stromal response is coevolving with cancer aggressiveness and supporting tumor progression.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This indicates that reactive stroma content can provide additional information beyond the Grade Group system used for current patient prognosis assessment in prostate cancer, which is in line with previous studies 6 9 , 11 . However, RSG is not entirely independent of Grade Group, as illustrated by our correlation analysis and previous studies 7 , 11 , 14 . This suggest that a reactive stromal response is coevolving with cancer aggressiveness and supporting tumor progression.…”
Section: Discussionsupporting
confidence: 47%
“…Smooth muscle differentiation markers such as calponin and desmin are commonly reduced in reactive stroma 3 , 5 , 9 , 10 , 13 . In contrast, vimentin, pro-collagen and tenascin-C, markers for activated fibroblasts and ECM remodeling, are elevated in reactive stroma in prostate cancer tissue 3 , 10 , 13 , 14 . Reactive stromal cells have also been suggested to promote angiogenesis in the tumor area 15 .…”
Section: Introductionmentioning
confidence: 92%
“…The findings from Reiter’ study demonstrated a coamplification of PSCA and MYC genes in PCa. PSCA and c‐Myc co‐expression was considered as a worse prognostic factor in PCa, and a marker of prostatic stem cells . c‐Myc had a profound impact on cell proliferation and differentiation, and its amplification played a key role in early prostate epithelia cell transformation and PCa growth .…”
Section: Discussionmentioning
confidence: 99%
“…8q amplicon, which was one of the most frequently amplified regions in human cancers. PSCA was approximately 15 Mb distal to Myc oncogene on 8q24, increased PSCA‐gene copy number in 71% (5 of 7 cases) of PCa with MYC gene amplification, PSCA, and c‐Myc were all considered to be markers of worse tumor prognosis, PSCA rs2294008 and c‐Myc rs9642880 were both significantly associated with the increased bladder cancer risk, suggesting that PSCA might interact with MYC gene, commonly induced the tumorigenesis and development. Therefore, in this study, we examined the expression pattern of PSCA and c‐Myc in PCa, investigated the effect of PSCA on PCa growth and cell cycle, and clarified its potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual absence of PSCA-immunoreactivity in the tumor stroma is an interesting finding, since e.g. in prostate cancer, PSCA-protein expression occurs not only in epithelial but also in stromal compartments [ 28 ]. Moreover, outside the prostate, immunohistochemical studies in normal human tissues reported on PSCA-staining in the bladder, stomach, colon and kidney [ 4 ].…”
Section: Discussionmentioning
confidence: 99%